Impact of corticosteroids on the efficacy of CD19/22 CAR-T cell therapy in pediatric patients with B-ALL: a single-center study - Yang, Jing; Zhang, Jing; Wan, Xinyu; Cai, Jiaoyang; Wang, Tianyi; Yang, Xiaomin; Li, Wenjie; Ding, Lixia; Song, Lili; Miao, Yan; Wang, Xiang; Ma, Yani; et al. (Frontiers in Pediatrics, 2025)
Introduction Corticosteroids are used for toxicity management, raising concerns about whether they may affect the anti-leukemic effects of chimeric antigen receptor (CAR)-T cells. Methods and results In this study, we retrospectively analyzed patients (fined two subgroups based on disease burden. Of the 75 cases in the low disease burden (LDB) group (MRD < 5%, no extramedullary disease), there was no significant difference between the use of steroids and event-free survival (EFS) (p = 0.21) and overall survival (OS) (p = 0.26), and the same was found for the 119 cases in the high disease burden (HDB) group. After eliminating the effect of consolidative transplantation on the prognosis, the EFS of the patients who did not use steroids was better (p = 0.037) in the LDB group, but the difference was not significant in the HDB group. The median cumulative dexamethasone-equivalent dose was 0.56 mg/kg, and the EFS and OS were similar in the different cumulative dose groups. Furthermore, there was no difference in the recovery of B cells and the expansion of CAR-T cell copies. Conclusion and discussion In conclusion, under the guidance of current CRS prevention and control measures, the rational use of corticosteroids does not affect the clinical efficacy and overall survival of CAR-T cell therapy in patients with B-ALL and also does not affect the persistence of CAR-T cells in vivo, but the dosage threshold needs further clinical or experimental verification.